Genotypical glioblastoma of the frontal lobe mimicking ganglioglioma: A case report and review of the literature. Issue 9 (30th August 2021) - Kraus, Theo F. J.; Pöppe, Johannes; Machegger, Lukas; Zellinger, Barbara; Dovjak, Eva; Schlicker, Hans U.; Schwartz, Christoph; Ladisich, Barbara; Spendel, Mathias; Al‐Schameri, Abdul R.; Winkler, Peter A.; Sotlar, Karl
Abstract: This case of severe phenotype‐genotype mismatch brain tumor morphologically mimicking benign ganglioglioma emphasizes the urgent need for advanced molecular profiling in brain tumor diagnosis in the era of sophisticated molecular profiling. Abstract : This case of severe phenotype‐genotype mismatch emphasizes the urgent need for advanced molecular profiling in brain tumor diagnosis in the era of sophisticated molecular profiling.